The Social Necessity Of Forming Patriotic Sentiment In The Context Of Globalization - Dusanov Noryigit Ernazarovich (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
In the contemporary era marked by accelerating globalization processes, the issues of national self-identification, preservation of historical memory, and safeguarding cultural heritage have gained particular relevance. Under such conditions, fostering patriotic sentiment emerges not only as an educational objective but also as a social necessity. This is because globalization, on the one hand, strengthens integration among nations, while on the other hand, it influences national identity and value systems. Therefore, cultivating a sense of national pride, civic responsibility, social engagement, and devotion to the homeland among younger generations constitutes an essential factor for social stability and spiritual development. A scientific study of this process makes it possible to identify effective mechanisms and pedagogical-psychological factors for the formation of patriotism.